2016
DOI: 10.1249/01.mss.0000488095.48094.60
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Response To Down-hill Running Exercise In Humans

Abstract: To determine the effects of exercise-induced muscle damage, we examined irisin responses during level running (LR), with less muscle damage, and downhill running (DHR), with greater muscle damage under equivalent exercise duration and oxygen consumption (V 3 O2) conditions.[Methods] Fifteen healthy men (age: 21.6 ± 2.0 y, height: 170 ± 1.3 cm, weight: 64.8 ± 2.7 kg) were randomly assigned to either the LR group (n = 8) or the DHR group (n = 7). Subjects in the LR group performed treadmill running at 70% of max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Based on existing studies, exercise type (endurance/ resistance), exercise time (acute/chronic), exercise intensity, and personal training prior to participation in studies count as factors affecting the circulating irisin level. Indeed, different studies have reported physical exercise influences are significant in irisin circulation levels [8][9][10], while other studies show that exercise, acute and/or chronic, has no substantial effect on blood irisin level [11][12][13]. Therefore, the role of exercise on irisin activity has been a controversial subject [14][15][16][17].…”
Section: The Influence Of Concurrent Training Intensity On Serum Irismentioning
confidence: 99%
“…Based on existing studies, exercise type (endurance/ resistance), exercise time (acute/chronic), exercise intensity, and personal training prior to participation in studies count as factors affecting the circulating irisin level. Indeed, different studies have reported physical exercise influences are significant in irisin circulation levels [8][9][10], while other studies show that exercise, acute and/or chronic, has no substantial effect on blood irisin level [11][12][13]. Therefore, the role of exercise on irisin activity has been a controversial subject [14][15][16][17].…”
Section: The Influence Of Concurrent Training Intensity On Serum Irismentioning
confidence: 99%